Immune and Metabolic Alterations in Liver Fibrosis: A Disruption of Oxygen Homeostasis? - Li, Xinyu; Zhang, Quyan; Wang, Zeyu; Zhuang, Quan; Zhao, Mingyi (Frontiers in Molecular Biosciences, 2022)
According to the WHO, "Cirrhosis of the liver" is the 11th leading cause of death globally in 2019. Many kinds of liver diseases can develop into liver cirrhosis and liver fibrosis is the main pathological presentation of different etiologies, including toxic damage, viral infection, and metabolic and genetic diseases. It is characterized by excessive synthesis and decreased decomposition of extracellular matrix (ECM). Cell death, hepatic stellate cells (HSCs) activation and inflammation are crucial incidences in the liver fibrosis. The process of fibrosis is also closely related to metabolic and immune disorders, which usually induced by the destruction of oxygen homeostasis, including mitochondrial dysfunction, oxidative stress, and hypoxia signaling pathway activating. Mitochondria are important organelles in energy generation and metabolism. Hypoxia-inducible factors (HIFs) are key factors activated when hypoxia. Both are considered as essential factors of liver fibrosis. Metabolism and hypoxia could also regulate of the activation immune cells, influencing inflammation in liver. In this review, the authors highlight the molecular mechanism for immune, metabolism and oxygen homeostasis in liver fibrosis as well as potential novel targets for antifibrotic therapies.